Photoplethysmogram Analysis and Applications: An Integrative Review - Park, Junyung; Seok, Hyeon Seok; Kim, Sang-Su; Shin, Hangsik (Frontiers in Physiology, 2022)
Beyond its use in the clinical environment, the photoplethysmogram is increasingly used for the purpose of measuring the physiological state of an individual in daily life. This review aims to examine existing research of the photoplethysmogram concerning its generation mechanisms, measurement principles, clinical applications, noise definition, pre-processing techniques, feature detection techniques, and post-processing techniques for photoplethysmogram processing, especially from an engineering point of view. We performed an extensive search of the PubMed, Google Scholar, Institute of Electrical and Electronics Engineers (IEEE), ScienceDirect, and Web of Science databases. The exclusion conditions did not include the year of publication, but articles not published in English were excluded. Based on 118 articles, we identified four main topics of enabling the PPG: (A) PPG waveform, (B) PPG features and clinical applications, including basic features based on the original PPG waveform, combined features of the PPG, and derivative features of the PPG, (C) PPG noise, including motion artifact baseline wandering and hypoperfusion, and (D) PPG signal processing, including PPG preprocessing, PPG peak detection, and signal quality index. The application field of the photoplethysmogram has been extending beyond the clinical to the mobile environment. Although there is no standardized preprocessing pipeline for PPG signal processing, as PPG data is acquired and accumulated in various ways, the recently proposed machine learning-based method is expected to offer a promising solution.